- #1

- 168

- 0

## Main Question or Discussion Point

Hi,

Is there a formula to do this? The textbook just says to "reverse" the action of T to get T^-1 (T inverse). Can someone explain to me in laymen terms, how to accomplish this? For example,

For T = [2x y]^T is T^-1 = [-2x y]^T?

Is there a formula to do this? The textbook just says to "reverse" the action of T to get T^-1 (T inverse). Can someone explain to me in laymen terms, how to accomplish this? For example,

For T = [2x y]^T is T^-1 = [-2x y]^T?